Design and simulation of top-contact structure organic Thin-film transistor for Nanoelectronics application - Khairul Anuar Mohamad (Universiti Malaysia Sabah, 2015)
Organic thin-film transistor (OTFT) performance has become more and more developed and improved over the years thus undeniably attracting the interest of more researches to enhance more its proficiency and applications. First, this report shown the comparison of electrical characteristics and fitness of the analytical model simulation with the experimental data obtained to study more thoroughly of the characteristics of OTFT. The analytical model simulation was done using a fixed parameters that is also used in the experimental data and was plotted using both saturation and linear region equations. Both the parameters and equations were simulated using MATIAB, where the metal oxide semiconductor field effect transistor (MOSFET) equations were modified to fit the simulation of the OTFT. The comparison analysis on threshold voltage and carrier mobility parameters was done. Then, the OTFTswere designed and simulated using the available basic TCAD tools; Silva co Device Editor (DevEdit). Pentacenebased organic transistorswere performed for top contact structure using Silvaco DevEdit with channel length of 60 IJm. The electrical characteristics of the pentacene-based organic transistors was evaluated from the output and transfer characteristics. Electrical parameters have been evaluated in terms of drain current, threshold voltage, mobility and on/off current ratio. Furthermore, the pattern of electrical characteristics of the devices exhibited similar behaviour to the inorganic transistor. Although OTFTs are not intended to replace current technology rather complement conventional technology for existing or emerging thin-film transistor applications, pentacene-based OTFTs are considered as one of the promising devices for future development of electronics application.